2007
DOI: 10.1074/jbc.m706007200
|View full text |Cite
|
Sign up to set email alerts
|

p56Lck Tyrosine Kinase Enhances the Assembly of Death-inducing Signaling Complex during Fas-mediated Apoptosis

Abstract: Although the death-inducing signaling complex (DISC) is rapidly assembled, several lines of evidence suggest that formation of this complex is not the first consequence of cell surface CD95 (Fas) stimulation but rather a later step in this process. Activation of Fas triggers a cascade of signaling events that culminate in cellular apoptosis. Tyrosine kinases are critical effectors in T cell activation. However, their functional involvement in death receptor-mediated apoptosis is unknown. Here, we used p56Lck -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(60 reference statements)
1
6
1
1
Order By: Relevance
“…Those results confirms the possible involvement of p56lck and/or downstream kinases in our model. Other studies have demonstrated that the tyrosine kinase p56lck is involved in the regulation of apoptosis induced by the mitochondrial pathway [114][115][116]. In our study, nuclear apoptosis was induced in p56lck-deficient cells exposed to TBT, suggesting that p56lck does not have a direct role in CD45-cells resistant to nuclear apoptosis [98].…”
Section: Involvement Of Cd45 In the Regulation Of The Intrinsic Mitoccontrasting
confidence: 61%
“…Those results confirms the possible involvement of p56lck and/or downstream kinases in our model. Other studies have demonstrated that the tyrosine kinase p56lck is involved in the regulation of apoptosis induced by the mitochondrial pathway [114][115][116]. In our study, nuclear apoptosis was induced in p56lck-deficient cells exposed to TBT, suggesting that p56lck does not have a direct role in CD45-cells resistant to nuclear apoptosis [98].…”
Section: Involvement Of Cd45 In the Regulation Of The Intrinsic Mitoccontrasting
confidence: 61%
“…PLC-γ1 interaction with the Fas receptor was transient, and reflected its activation pattern in response to Fas receptor stimulation. As shown by others, Lck was found to be preassociated with the Fas signaling complex in untreated cells (17). Interestingly, Fas ligand stimulation rapidly decreased the amount of total and activated Lck copurifying with the Fas receptor (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…While the kinase activity of Lck has been reported to be required for Jurkat T-cell apoptosis in response to some apoptogenic stimuli [13,14,20,40], other stimuli are known to induce apoptosis independently of Lck activity [16,21]. To address the requirement for the catalytic activity of Lck in A23187-dependent apoptosis of Jurkat cells, we used Jurkat and JCaM1 cells stably expressing a constitutively active Lck mutant (Y505F) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms underlying T-cell priming to apoptosis by p66Shc have yet to be fully understood. We investigated the potential involvement of Lck, a Src family kinase which has been implicated in lymphocyte apoptosis induced by various stimuli [11][12][13][14][15][16][19][20][21], in the proapoptotic activity of p66Shc in Jurkat T cells. To specifically dissect the link between p66Shc and Lck we used JCaM1.6 cells, which lack expression of both Lck and p66Shc, stably transfected with either empty vector (JCaM1) or a vector encoding wild-type p66Shc (JCaM1 p66 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation